Assessment of Alveolar Bone Dimensions in Immediate Versus Staged Reconstruction in Sites with Implant Failure - Heera Lee; Somyeong Hwa; Youngkyung Ko; Jun-Beom Park (Applied Sciences, 2025)
Evaluating the implant site immediately after implant removal is crucial for assessing its condition and ensuring morphological stability. Immediate reconstruction at the time of implant removal has been proposed as a strategy to preserve alveolar ridge width. This study aims to evaluate whether immediate alveolar bone reconstruction at the time of implant removal provides comparable or superior dimensional stability of the alveolar ridge compared to staged reconstruction approaches. The null hypothesis of this study is that there is no significant difference in alveolar bone dimensions between immediate and staged reconstructions following implant removal. This retrospective study included seven participants, consisting of six males and one female. The participants were categorized into three groups based on the treatment approach following implant removal. In Group 1, no bone grafting was performed after implant removal. In Group 2, bone grafting was conducted following implant removal, with an adequate healing period before implant placement. In Group 3, bone grafting was performed simultaneously with implant removal. Cone-beam computed tomography (CBCT) imaging was conducted before implant removal (T0), after implant removal or bone grafting (T1), and after implant placement (T2). All removed implants were successfully replaced with new ones, regardless of bone grafting. In terms of alveolar ridge width at 1 mm below the crest, Group 1 exhibited the greatest reduction (ΔT1 − T0 = −5.1 ± 3.7 mm), while Group 2 showed a mild increase (+1.1 ± 2.6 mm), and Group 3 had a moderate decrease (−1.3 ± 1.0 mm). This suggests that delayed bone grafting can better preserve or enhance bone volume during healing. A reduction in buccal ridge height between T1 and T0 (ΔT1 − T0) was observed, particularly in Group 1. In contrast, an increase in buccal ridge height was most pronounced in Group 2. Although immediate reconstruction (Group 3) did not result in statistically significant gains, it achieved successful implant placement without complications and reduced the total treatment duration, which might be beneficial from a clinical efficiency and patient satisfaction standpoint. Therefore, staged bone grafting (Group 2) appears to offer greater dimensional stability, particularly in maintaining ridge height, whereas immediate reconstruction (Group 3) remains a clinically viable alternative for stable healing in select cases, especially when shorter treatment timelines are prioritized.